Embidobia Ashmead (Hymenoptera, Platygastroidea, Scelionidae) of the Indian region with descriptions of new species - Kamalanathan Veenakumari; Sreedevi Kolla; Satya Nand Sushil; Duleep Kumar Samuel; Farmanur Rahman Khan; Prashanth Mohanraj (European Journal of Taxonomy)
Embidobia (Platygastroidea: Scelionidae) are known to be egg parasitoids of Embioptera. The type species Embidobia urichi was described by Ashmead in 1896. In the last 127 years, eleven species of Embidobia were described worldwide of which two (Embidobia brittanica Girault, 1917 and E. orientalis Dodd, 1939) are from the Oriental region. While the former was described from India, the latter was from Sri Lanka. In this paper we describe 13 new species from India – Embidobia agastya Veenakumari sp. nov., E. barbarika Veenakumari sp. nov., E. dooranetra Veenakumari sp. nov., E. gauriputra Veenakumari sp. nov., E. hiranya Veenakumari sp. nov., E. hrdaya Veenakumari sp. nov., E. jatayu Veenakumari sp. nov., E. mahabali Veenakumari sp. nov., E. omkara Veenakumari sp. nov., E. procera Veenakumari sp. nov., E. sankirna Veenakumari sp. nov., E. saroma Veenakumari sp. nov. and E. yuyutsu Veenakumari sp. nov. The two previously known species, E. orientalis and E. brittanica, are redescribed. A key to the females of all Oriental species is provided along with illustrations.